Excess and the mean in early modern English literature - Scodel, Joshua, 1958- (Literature in history (Princeton, N.J.), 2002)
This book examines how English writers from the Elizabethan period to the Restoration transformed and contested the ancient ideal of the virtuous mean. As early modern authors learned at grammar school and university, Aristotle and other classical thinkers praised "golden means" balanced between extremes: courage, for example, as opposed to cowardice or recklessness. By uncovering the enormous variety of English responses to this ethical doctrine, Joshua Scodel revises our understanding of the vital interaction between classical thought and early modern literary culture. --From publisher's description